Castor oil-based polyurethanes containing cellulose nanocrystals - Wik, Vera M. (2011)
Partially foamed and nanocellulose-reinforced polyurethanes (PU) based on castor oil (CO) were prepared and their different properties were measured and related to their structures. A castor oil-based polyol (COPO) was obtained by alcoholysis of CO with triethanolamine. The COPO was used in the preparation of partially foamed and solid PU. Cellulose nanofibrils (NC) in the range of the rheological percolation content were incorporated to the materials and the final mechanical properties of these nanocomposites were analyzed. The incorporated NC considerably affected the rheology of the suspensions, which presented solid-like behavior under frequency sweep tests with the addition of only 0.5 wt% of NC. By increasing the NC concentration the dispersion becomes increasingly difficult. The properties of the solid PU were also affected by the incorporation of NC and a significant increase of the tensile modulus was observed for the 0.5 wt% NC composite, compared to the unfilled solid PU. This behavior was associated to the incorporation of the rigid particle reinforcement and the interfacial bonding. As expected, the partially foamed PU showed lower modulus than the corresponding solid PU.